2017
DOI: 10.2967/jnumed.112.114397
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radionuclide Imaging in Epilepsy, Part 1: Sporadic Temporal and Extratemporal Lobe Epilepsy

Abstract: CE credit: For CE credit, you can access the test for this article, as well as additional JNMT CE tests, online at https://www.snmmilearningcenter.org. Complete the test online no later than March 2020. Your online test will be scored immediately. You may make 3 attempts to pass the test and must answer 80% of the questions correctly to receive 1.0 CEH (Continuing Education Hour) credit. SNMMI members will have their CEH credit added to their VOICE transcript automatically; nonmembers will be able to print out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 73 publications
0
88
0
Order By: Relevance
“…In epilepsy patients during interictal period, [ 18 F] FDG PET typically shows reduced metabolic activity in the epileptogenic region (Wong et al, 2010;Kumar and Chugani, 2013;Ding et al, 2014). In addition, hypometabolism in temporal areas seems to be a common feature found in different animal models of epilepsy Virdee et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…In epilepsy patients during interictal period, [ 18 F] FDG PET typically shows reduced metabolic activity in the epileptogenic region (Wong et al, 2010;Kumar and Chugani, 2013;Ding et al, 2014). In addition, hypometabolism in temporal areas seems to be a common feature found in different animal models of epilepsy Virdee et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…It is characterized by microscopic abnormalities in cortical lamination, neuronal differentiation, and neuronal maturation anomalies, that can be difficult to detect/be undetectable, even on highfield MRI [52][53][54][55][56]. In our cohort, pathological analysis revealed that all patients had FCD type 1, which is usually more difficult to detect on MRI than type 2.…”
Section: Doi: 101159/000487088mentioning
confidence: 89%
“…For example, a focus in the mesial temporal lobe can be associated with hypometabolism throughout the anterior temporal lobe [52,53]. Other regions of the brain may show alterations in metabolic activity [42,54]. Decreased metabolic activity in the contralateral cerebellum (diaschisis) is more commonly seen with an epileptogenic focus in the frontal or parietal lobe.…”
Section: Ictal Spectmentioning
confidence: 98%
“…5, 6). If fully developed, this approach could increase the proportion of successful ictal SPECTs [35,[37][38][39][40][41][42][43][44][45].…”
Section: Ictal Spectmentioning
confidence: 98%
See 1 more Smart Citation